2006
DOI: 10.1248/yakushi.126.1383
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Shikonin on Human Breast Cancer Cells Proliferation and Apoptosis In Vitro

Abstract: Shikonin, isolated from the plant Lithospermum erythrorhizon Sieb. Et Zucc, has been reported to induce apoptosis in several tumor cells. However, such eŠect of shikonin on human breast cancer cells has not been reported. Thus, in the present study, whether shikonin could induce MCF-7 human breast cancer cell apoptosis was investigated. The results showed that shikonin (2.5-80 mM) induced MCF-7 cell death in a time-and dose-dependent manner, as measured by MTT assay. The IC 50 of a 24 h, 48 h and 72 h time cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 12 publications
1
35
0
Order By: Relevance
“…Shikonin-rendered cell apoptosis through activation of a caspase-dependent pathway was found in HL60 human leukemia cells, 10) malignant melanoma cells, 13) Hela cells, 11) colorectal cancer, 17) and breast cancer. 30) Indeed, shikonin diminished the cell proliferation of 143B osteosarcoma cells in a dose-and time-dependent manner. Shikonininduced apoptosis in 143B osteosarcoma cells was evidenced by an increased sub-G1 population and enhanced DNA condensation.…”
Section: Discussionmentioning
confidence: 97%
“…Shikonin-rendered cell apoptosis through activation of a caspase-dependent pathway was found in HL60 human leukemia cells, 10) malignant melanoma cells, 13) Hela cells, 11) colorectal cancer, 17) and breast cancer. 30) Indeed, shikonin diminished the cell proliferation of 143B osteosarcoma cells in a dose-and time-dependent manner. Shikonininduced apoptosis in 143B osteosarcoma cells was evidenced by an increased sub-G1 population and enhanced DNA condensation.…”
Section: Discussionmentioning
confidence: 97%
“…Cell samples were incubated at 4°C in the dark for at least 15 m, and analyzed by a FACScan ‰ow cytometer (Becton Dickinson). 13) Data Analysis Results were expressed as mean ±SD. Statistical signiˆcance ( p<0.05) was assessed by one-way ANOVA followed by least signiˆcant diŠerence method (SPSS12.0 software, SPSS, USA).…”
Section: Cell Culturementioning
confidence: 99%
“…Han et al (2007) showed that shikonin stimulated cell death in MCF-7 and HEK293 cancer lines distinct from apoptosis but accompanied with (a) a morphology of necrotic cell death; (b) loss of plasma membrane integrity; (c) loss of mitochondrial membrane potentials; (d) activation of autophagy as a downstream consequence of cell death, but not a causal factor. Anticancer activitiy of shikonin and/or its derivatives has been indicated by other studies as well (Zhang et al 2005;Hou et al 2006). Acetylshikonin isolated from A. euchroma cell suspension cultures exhibited specific in vivo and in vitro antitumor effects (Xiong et al 2009 (1), alkannin (2), shikonin (3), catechin (4), isorhamnetin (5), hypericin (6), hyperforin (7), podophyllotoxin (8), emodin (9), rhein (10) Phytochem Rev (2011) 10:309-323 313 acetylshikonin inhibited K562 and HL-60 tumor growth (Xuan and Hu 2009).…”
mentioning
confidence: 77%